Kahoot-Based Play Learning to Improve Students’ Interest in Islamic Religious Education: A Classroom Action Research - Fadillah Fadillah; Sri Jamilah; Irwan Irwan (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
Students’ learning interest in Islamic Religious Education (PAI) often tends to be low when the learning process is dominated by conventional teaching methods that provide limited interaction and engagement. The integration of digital learning media and play-based learning approaches is considered a promising strategy to create more engaging and participatory classroom environments. This study aims to analyze the implementation of the Kahoot application based on play-based learning to improve students’ learning interest in Islamic Religious Education. This research employed a Classroom Action Research (CAR) design involving 35 students of class XI.4 at State Senior High School 4 Bima City, West Nusa Tenggara, Indonesia. Data were collected through participatory observation, open-ended interviews, and documentation. The findings show that the integration of Kahoot with play-based learning strategies significantly increased students’ participation and engagement in PAI learning. Participation increased from 20% in the pre-cycle stage to 77.14% in Cycle I, although it decreased to 62.86% in Cycle II due to technical constraints and student absenteeism. Overall, the learning process became more interactive and students showed greater enthusiasm toward the subject. Therefore, the implementation of Kahoot-based play learning can support the improvement of students’ learning interest in Islamic Religious Education. Future learning practices are recommended to strengthen technological infrastructure and classroom management to optimize the effectiveness of digital game-based learning.